Modelling rotavirus concentrations in rivers: Assessing Uganda's present and future microbial water quality. (1st October 2021) - Okaali, Daniel A.; Kroeze, Carolien; Medema, Gertjan; Burek, Peter; Murphy, Heather; Tumwebaze, Innocent K.; Rose, Joan B.; Verbyla, Matthew E.; Sewagudde, Sowed; Hofstra, Nynke
Highlights: Present and future rotavirus concentrations in Uganda's rivers are simulated. Key sources are open defecation, limited treatment of wastewater and faecal sludge. A hotspot is identified as a densely populated area with poor sanitation coverage. Population growth and urbanization affect concentrations more than climate change. Robust sanitation improvements are required to improve microbial water quality. Abstract: Faecal pathogens can be introduced into surface water through open defecation, illegal disposal and inadequate treatment of faecal sludge and wastewater. Despite sanitation improvements, poor countries are progressing slowly towards the United Nation's Sustainable Development Goal 6 by 2030. Sanitation-associated pathogenic contamination of surface waters impacted by future population growth, urbanization and climate change receive limited attention. Therefore, a model simulating human rotavirus river inputs and concentrations was developed combining population density, sanitation coverage, rotavirus incidence, wastewater treatment and environmental survival data, and applied to Uganda. Complementary surface runoff and river discharge data were used to produce spatially explicit rotavirus outputs for the year 2015 and for two scenarios in 2050. Urban open defecation contributed 87%, sewers 9% and illegal faecal sludge disposal 3% to the annual 15.6 log10 rotavirus river inputs in 2015. Monthly concentrations fell between -3.7 (Q5) and 2.6 (Q95) log10 particles per litre, with 1.0 and 2.0 median and mean log10 particles per litre, respectively. Spatially explicit outputs on 0.0833 × 0.0833° grids revealed hotspots as densely populated urban areas. Future population growth, urbanization and poor sanitation were stronger drivers of rotavirus concentrations in rivers than climate change. The model and scenario analysis can be applied to other locations. Graphical abstract: Image, graphical abstract